ATTENTION TO PSYCHOLOGY IN UZBEKISTAN DURING THE YEARS OF INDEPENDENCE - Sharopova Madina Diyorjonovna (American Journals, 2022)
This article deals with the attention to Psychology in Uzbekistan during the years of independence, as well as the psychological reforms carried out before independence and the work of scientists.
Keywords: Independence, psychology, psychological research, research and articles, the development of psychology.